The Dual Role approach: encouraging access to community radio. (1st December 2008) - Gnnel, Traudel
During the last two decades, community radio has achieved a legal status within the media system of many European countries. Although it is committed to giving a voice to the voiceless, one of its major weaknesses is a social and gender bias: many stations have difficulties in involving the target groups they aim to address, for example, women and so-called socially disadvantaged groups (people with a migrant background, with limited school education, elderly people, homeless etc.). Strategies to involve those target groups seem to be missing. Drawing on the experience and the evaluation of three EU-funded projects, this article describes a training approach, which aims to encourage the involvement of disadvantaged groups in community radio. This consists of a learner-centred design, which links learning with doing: the dual role of participants during the course, who are at the same time both trainees and also future trainers. The underlying theory of the approach action oriented media pedagogy is outlined and the role and importance of participatory evaluation (research) are discussed.